Multiwavelength excitation Raman scattering analysis of bulk and two-dimensional MoS2: vibrational properties of atomically thin MoS2 layers. (7th July 2015) - Placidi, Marcel; Dimitrievska, Mirjana; Izquierdo-Roca, Victor; Fontané, Xavier; Castellanos-Gomez, Andres; Pérez-Tomás, Amador; Mestres, Narcis; Espindola-Rodriguez, Moises; López-Marino, Simon; Neuschitzer, Markus; Bermudez, Veronica; Yaremko, Anatoliy; et al.
Abstract: In order to deepen the knowledge of the vibrational properties of two-dimensional (2D) MoS2 atomic layers, a complete and systematic Raman scattering analysis has been performed using both bulk single-crystal MoS2 samples and atomically thin MoS2 layers. Raman spectra have been measured under non-resonant and resonant conditions using seven different excitation wavelengths from near-infrared (NIR) to ultraviolet (UV). These measurements have allowed us to observe and identify 41 peaks, among which 22 have not been previously experimentally observed for this compound, and characterize the existence of different resonant excitation conditions for the different excitation wavelengths. This has also included the first analysis of resonant Raman spectra that are achieved using UV excitation conditions. In addition, the analysis of atomically thin MoS2 layers has corroborated the higher potential of UV resonant Raman scattering measurements for the non-destructive assessment of 2D MoS2 samples. Analysis of the relative integral intensity of the additional first- and second-order peaks measured under UV resonant excitation conditions is proposed for the non-destructive characterization of the thickness of the layers, complementing previous studies based on the changes of the peak frequencies.